A superhydrophilic nitinol shape memory alloy with enhanced anti-biofouling and anti-corrosion properties. Issue 5 (27th May 2016) - Song, K.; Min, T.; Jung, J.-Y.; Shin, D.; Nam, Y.
Abstract: This work reports on a nitinol (NiTi) surface modification scheme based on a chemical oxidation method, and characterizes its effects on wetting, biofouling and corrosion. The scheme developed is also compared with selected previous oxidation methods. The proposed method turns NiTi into superhydrophilic in ~5 min, and the static contact angle and contact angle hysteresis were measured to be ~7° and ~12°, respectively. In the PRP (platelet rich plasma) test, platelet adhesion was reduced by ~89% and ~77% respectively, compared with the original NiTi and the NiTi treated with the previous chemical oxidation scheme. The method developed provides a high (~1.1 V) breakdown voltage, which surpasses the ASTM standard for intervascular medical devices. It also provides higher superhydrophilicity, hemo-compatibility and anti-corrosion resistance than previous oxidation schemes, with a significantly reduced process time (~5 min), and will help the development of high performance NiTi devices.